Crafting Resonance in a Sports Media Event: The Olympic Games as a transnational social drama. (17th February 2019) - Liang, Limin
Abstract : Through studying the turn from conflict to function in one of the most expensive media events in history, the Beijing Olympics, and by building on Jeffrey Alexander's cultural pragmatics theory, the article proposes a theoretical framework for studying mega-events as a transnational social drama, i.e, a strategic contest whereby media engage social institutions in stylistic but contentious public performances. Eventually, which performance stands out as resonant is contingent upon the script, the actors, the audience, the mise-en-scène, and social power. Initially, the performance of Free Tibet protesters was judged to be more authentic through coherent media framing. But the subsequent redress phase saw a return of the affirmative narrative made possible by the redefinition of the mise-en-scène following the Wenchuan earthquake and authorities' enhanced capability in controlling symbolic production. The Chinese performance came to be seen as more or less authentic, hence strategic public diplomacy was transformed into a ritual-like experience. The article reads media events as neither a mythical system functioning in a consensual way nor merely an ideology serving instrumental interests. An interactional approach focusing on the contention among performers in which conflict may be ritualized, with media playing a crucial but not determining role, comes closer to explaining the course of the Games and similar global media events to come.